Application of material flow cost accounting (MFCA) and quality control tools in wooden toys product - Nakkiew W. (2017)
© IEOM Society International. Small to medium enterprise (SME) in Thailand contributes significantly to the Thai economy. However, a large portion of the SME companies do not have systematic productivity improvement mechanism inside their organizations. The lack of appropriate productivity improvement tools results in lots of wastes in several kinds of resources such as material, energy, time, and so on throughout the production system. Material Flow Cost Accounting (MFCA) is an international standard tool (ISO 14051, since 2011), described as an internal decision making tool aiming for the reduction of material and resources input coming into the system. In this research a SME company, a wooden toy company, in Chiang Mai, Thailand was used as a case study for the application of MFCA concept. The results from the MFCA analysis alone could only identify the point of major wastes with their associated costs in materials, energy, and labor. In order for a company to fully utilize the results from the MFCA analysis, a further analysis about the root cause and a systematic methodology for obtaining appropriate solutions for the root causes must be conducted. Quality Control tools, usually called 7 QC tools, were used to obtain root cause and possible solution to the problem. Results from the MFCA analysis for a wooden toy company in this research showed that the wastes accounted from 58.07% of the total cost. Two of the most significant processes are the cutting process and the drilling process which provided most negative costs comparing with other processes: 70,960 Baht per lot and 32,699 Baht per lot for cutting and drilling processes, respectively. After obtaining root causes and their possible solution by the application of 7QC tools, two possible solutions are adopted by the company. For the cutting process, the size of the raw material purchased from vendor was changed and for the drilling process a new jig-fixture was introduced. By changing the size of the raw material from the vendor the company reduced a significant amount of wastes and saved 45,008 Baht per lot. By introducing a new jig-fixture for the drilling process, the time was reduced significantly resulting in labor and energy cost saving of 1,897 Baht per lot. © IEOM Society International.